2007
DOI: 10.1016/j.jacc.2006.11.048
|View full text |Cite
|
Sign up to set email alerts
|

The Final 10-Year Follow-Up Results From the BARI Randomized Trial

Abstract: There was no significant long-term disadvantage regarding mortality or myocardial infarction associated with an initial strategy of PTCA compared with CABG. Among patients with treated diabetes, CABG conferred long-term survival benefit, whereas the 2 initial strategies were equivalent regarding survival for patients without diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(61 citation statements)
references
References 16 publications
1
56
2
2
Order By: Relevance
“…• In BARI 2D study [79,80] authors randomized 2,368 patients with type 2 diabetes and chronic coronary artery disease to initial strategy of optimal medical therapy or medical treatment with percutaneous or surgical revascularization. There was no difference between groups in relation to survival in a follow-up of 5 years (87.8% in the medical therapy group vs. 88.3% in the revascularized group, p = 0.97).…”
Section: Methodsmentioning
confidence: 99%
“…• In BARI 2D study [79,80] authors randomized 2,368 patients with type 2 diabetes and chronic coronary artery disease to initial strategy of optimal medical therapy or medical treatment with percutaneous or surgical revascularization. There was no difference between groups in relation to survival in a follow-up of 5 years (87.8% in the medical therapy group vs. 88.3% in the revascularized group, p = 0.97).…”
Section: Methodsmentioning
confidence: 99%
“…The 10-year results of the BARI [9] showed that there was no significant long-term disadvantage regarding mortality or myocardial infarction associated with an initial strategy of PCI compared with CABG. Among patients with treated diabetes, CABG conferred long term survival benefit, whereas the 2 initial strategies were equivalent regarding survival for patients without diabetes.…”
Section: Bari (Bypass Angioplasty Revascularization Investigation)mentioning
confidence: 99%
“…The survival benefit of CABG in patients with diabetes persisted at 10 years (PTCA 45.5% vs. CABG 57.8%, P =0.025) [17]. In an analysis based on pooled individual patient data from 10 randomized trials comparing CABG with PCI (median follow-up of 5.9 years), mortality among patients with DM was 30% lower in the CABG group than in the PCI group (hazard ratio [HR] 0.70; 95% CI 0.56–0.87; P =0.014 for the interaction between DM and type of revascularization) [18].…”
Section: Cabg Versus Pci In Multivessel Cadmentioning
confidence: 99%
“…Importantly, follow-up at 1-year may not yet reflect the true long-term differences between CABG and DES treatment of patients with DM because previous reports demonstrated reduced long-term mortality in CABG compared with PCI [17,18]. Finally, few data are available with regard to the long-term clinical implications and risks associated with of the ‘softer’ endpoint of repeat revascularization.…”
Section: Cabg Versus Pci In Multivessel Cadmentioning
confidence: 99%